Recognition of the discipline of conservation mycology - Tom W. May; Jerry A. Cooper; Anders Dahlberg; Giuliana Furci; David W. Minter; Gregory M. Mueller; Alison Pouliot; Zhuliang Yang (Conservation Biology, 2019)
Article impact statement : Conservation mycology is a newly introduced discipline relevant to conservation biologists, mycologists, ecologists, and conservation policy.